The music of theology : language - space - silence - Hass, Andrew; Kate, Laurens ten, 1958-; Martinson, Mattias (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book reconceives theology as a musical endeavour in critical tension with language, space and silence. An Overture first moves us from music to religion, and then from theology back to music - a circularity that, drawing upon history, sociology, phenomenology, and philosophy, disclaims any theology of music and instead pursues the music in theology. The chapters that follow explore the three central themes by way of theory, music and myth: Adorno, Benjamin and Deleuze (language), Derrida, Rosa and Nancy (space), Schelling/Hegel, Homer and Cage (silence). In overdubbing each other, these chapters work towards theology as a sonorous rhythm between loss and freedom. A Coda provides three brief musical examples - Thomas Tallis, György Ligeti, and Evan Parker - as manifestations of this rhythm, to show in summary how music becomes the very pulse of theology, and theology the very intuition of music. The authors offer an interdisciplinary engagement addressing fundamental questions of the self and the other, of humanity and the divine, in a deconstruction of modern culture and of its bias towards the eye over the ear. The book harmonizes three scholarly voices who attempt to find where the resonance of our Western conceptions and practice, musically and theologically, might resound anew as a more expansive music of theology"--
Keywords: Theology; Music theory -- Philosophy; Music -- Philosophy and aesthetics; Music -- Religious aspects -- Christianity; RELIGION / Christianity / Literature; RELIGION / Christianity / Theology / General; MUSIC / Religious / General